Further insights on endogenous money and the liquidity preference theory of interest. Issue 4 (2nd October 2019) - Lavoie, Marc; Reissl, Severin
Abstract: We present a simple stock-flow consistent (SFC) model to discuss some recent claims made by Angel Asensio in a paper published in this journal regarding the relationship between endogenous money theory and the liquidity preference theory of the rate of interest. We incorporate Asensio's assumptions as far as possible and use simulation experiments to investigate his arguments regarding the presence of a crowding-out effect, the relationship between interest rates and credit demand, and the ability of the central bank to steer interest rates through varying the stock of money. We show that in a fully-specified SFC model, some of Asensio's conclusions are not generally valid (most importantly, the presence of a crowding-out effect is ambiguous), and that in any case, his use of a non-SFC framework leads him to leave aside important mechanisms which can contribute to a better understanding of the behavior of interest rates. More generally, this paper once more demonstrates the utility of the SFC approach in research on monetary economics.